2011
DOI: 10.1007/s00423-011-0878-4
|View full text |Cite
|
Sign up to set email alerts
|

High-dose immunoglobulin preparations improve survival in a CLP-induced rat model of sepsis

Abstract: Our results suggest that high-dose immunoglobulin therapy may improve the serum endotoxin and HMGB1 levels and overall survival rate in sepsis by inhibiting the inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 34 publications
1
6
0
Order By: Relevance
“…The data in the present study also demonstrated that IVIG treatment reduces the levels of two pro-inflammatory cytokines (TNF-α, and IL-6). This findings is consistent with previous studies 10,11,34 . In our study, the degree of cytokine reduction was not necessarily dependent on the IVIG dose.…”
Section: Hagiwara Et Al and Yoshikawa Et Al Have Suggested That Immsupporting
confidence: 94%
See 2 more Smart Citations
“…The data in the present study also demonstrated that IVIG treatment reduces the levels of two pro-inflammatory cytokines (TNF-α, and IL-6). This findings is consistent with previous studies 10,11,34 . In our study, the degree of cytokine reduction was not necessarily dependent on the IVIG dose.…”
Section: Hagiwara Et Al and Yoshikawa Et Al Have Suggested That Immsupporting
confidence: 94%
“…The Fab-dependent effects include neutralization of bacteria, neutralization of bacterial toxins, neutralization of bacterial superantigens, suppression of cytokines produced by immune cells, and autoantibodies 29 . Previous studies have also shown IVIG has an anti-inflammatory effect 10,11,[30][31][32][33] . Thus, immunoglobulins could theoretically improve survival in our mouse sepsis model not only through direct antibacterial effects but also by exerting anti-inflammatory effects.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…In recent years, immunoglobulin preparations have been utilized in patients with severe sepsis or septic shock (NorrbyTeglund et al, 2006;Yoshikawa et al, 2012). IgM-enriched IVIG contains Ig M, Ig A, and Ig G and it was shown that IgM-enriched IVIG (250 mg/kg) is more efficient than standard IgG IVIG in terms of toxin neutralization and bacterial agglutination in cases with superantigen-mediated sepsis (Darenberg et al, 2004;Norrby-Teglund et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Gao et al (2012) have noted a significant increase of aST, alT, lDH, CK and creatinine serum level 12 hours from the Clp procedure in rats. Yoshikawa et al (2012) demonstrated that treatment with a high-dose of human immunoglobulin (1.500 mg/kg) significantly improves the survival of rats in the Clp model. based on correlation analysis of measured parameters, it was concluded that body temperature (T), blood urea nitrogen (bUN), creatinine, alT, CK, Il-6 and mCp-1 levels after the Clp were negatively correlated with survival, while platelet count (plT), Hmgb1 and granulocyte-macrophage colony stimulating factor (gmCCf) were positively correlated with the survival outcome.…”
Section: Resultsmentioning
confidence: 66%